ChemInform Abstract: Discovery of γ‐MnP4 and the Polymorphism of Manganese Tetraphosphide. Issue 46 (November 2015) - Henge, Dennis B.; Hermus, Martin; Litterscheid, Christian F.; Wagner, Norbert; Beck, Johannes; Albert, Barbara; Brgoch, Jakoah
Abstract The new title polymorph of MnP4 is synthesized by chemical vapor transport of a stoichiometric mixture of manganese and red phosphorus using iodine as transporting agent (evacuated silica tubes, temperature gradient 1073→923 K, 14 d).